Análisis de los mercados internacionales para la exportación de café en bolsas filtrantes desde el municipio Neiva, Huila. (2023)
The objective of this project entitled "analysis of international markets for the export of coffee in filter bags from Neiva, Huila" is to make the company Dugrato S.A.S aware of the possible international markets to start exporting and expand the company, as well as to give to know to the coffee growers of the Department of Huila a different, practical and innovative way when it comes to exporting a coveted product worldwide such as coffee. The department of Huila has been taking a greater position at the national level due to the fact that the participation of coffee exports has been increasing, this is due to the fact that it has climatic advantages, which make the coffee of better quality, aroma and flavor, while Obtaining these advantages seeks to take advantage of it and give added value to the product, and coffee in filter bags is a step towards this. In order to export, the productive capacity of the company and the characteristics of the product must be clear to achieve an analysis of how to enter the international market, where several factors must be taken into account, for this reason a market selection matrix is made, where the countries that have the greatest demand and are most suitable for export are analyzed and chosen, to finish, the requirements and documentation that the coffee needs to leave the national customs territory are studied, as well as the requirements that the destination country has for its income.